Corporate Governance Transfer and Synergistic Gains from Mergers and Acquisitions - Wang, Cong; Xie, Fei (Review of Financial Studies, 2009)
We present evidence on the benefits of changes in control from mergers and acquisitions. We find that the stronger the acquirer's shareholder rights relative to the target's, the higher the synergy created by an acquisition. This result supports the hypothesis that acquisitions of firms with poor corporate governance by firms with good corporate governance generate higher total gains. We also find that the synergy effect of corporate governance is shared by target shareholders and acquiring shareholders, in that both target returns and acquirer returns increase with the shareholder-rights difference between the acquirer and the target.